2015
DOI: 10.1074/jbc.m114.628420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phospholipids in Insulin Secretory Granules and Mitochondria in Pancreatic Beta Cells and Their Changes with Glucose Stimulation

Abstract: Background: Phospholipids in insulin granules were characterized. Results: Phosphatidylserine and phospholipids with unsaturated or short fatty acids were concentrated in granules and increased with glucose stimulation. Conclusion: Phosphatidylserine enhances the interaction between proteins in granules and plasma membranes. Unsaturated and short FA increase the fluidity and curvature of lipid bilayers. Significance: Fusion of granules to PM and insulin exocytosis is enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 87 publications
3
65
1
Order By: Relevance
“…Our recent study that characterized the phospholipid composition of insulin secretory granules (ISG) 2 of pancreatic beta cells suggested that ISG phosphatidylserine (PS) facilitates docking and fusion of the ISG with the plasma membrane during insulin exocytosis (1). We found that the concentration of PS in ISG is 5-fold that of the whole cell, and with glucose stimulation its concentration in ISG increases even more (1).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Our recent study that characterized the phospholipid composition of insulin secretory granules (ISG) 2 of pancreatic beta cells suggested that ISG phosphatidylserine (PS) facilitates docking and fusion of the ISG with the plasma membrane during insulin exocytosis (1). We found that the concentration of PS in ISG is 5-fold that of the whole cell, and with glucose stimulation its concentration in ISG increases even more (1).…”
mentioning
confidence: 87%
“…We found that the concentration of PS in ISG is 5-fold that of the whole cell, and with glucose stimulation its concentration in ISG increases even more (1). PS is the most abundant negatively charged phospholipid in most cells, including in the beta cell (1), and the concentration of PS in the plasma membrane of most cells is known to be high.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The intracellular trafficking process exposes ZnT8 to a dynamic lipid composition as subcellular membrane compartments undergo enormous lipid remodeling, resulting in enrichments of anionic phosphatidylinositol (PI), phosphatidylserine (PS), non-bilayer lysophosphatidylcholine (LPC), and cholesterol in insulin granules (16) (Fig. 4a).…”
Section: Functional Modulation Of Human Znt8mentioning
confidence: 99%
“…4b and Table 1). LPC is highly enriched in insulin granules, accounting for 20% of total granule lipids (16). When inserted into the lipid bilayer, the cone-shaped LPC introduces positive curvature.…”
Section: Functional Modulation Of Human Znt8mentioning
confidence: 99%